Secretion and assembly of functional mini-cellulosomes from synthetic chromosomal operons in Clostridium acetobutylicum ATCC 824 - Kovacs, Katalin; Willson, Benjamin J.; Schwarz, Katrin; Heap, John T.; Jackson, Adam; Bolam, David N.; Winzer, Klaus; Minton, Nigel P. (2013)
BACKGROUND: